Adoption of Post-Harvest Management Practices by Vegetable Growers in Haryana State (Indian Journal of Extension Education, 2017)
Vegetables are not only commercially important and nutritionally essential food commodities due to major dietary source of vitamins, sugars, organic acids, and minerals, and also other phytochemicals including dietary fiber and antioxidants with health-beneficial effect. It has created high demand for fresh vegetables but major challenge in meeting this high demand for fresh vegetables is postharvest losses which account about 30.00 per cent in India. Avast quantity of vegetables is destroying every year due to farmers’ lack of knowledge about post harvest technologies. To meet the domestic a well as the export demands of vegetables it is essential to integrate the various technologies from production to post-harvest. The study revealed that majority of the respondents (51.7%) belonged to ’moderate’ category of awareness pertaining to PHM practices. They were aware of the practices such as vegetable fruit should not be thrown but put carefully, it is better to harvest vegetables at coolest part of the day, cleaning and sorting is necessary for high shelf life, grading is necessary for getting high market price whereas less aware of PHM practices such as sorting of thick necked onion bulbs, vegetable fruit not to be pulled but clipped with sharp knife or secateurs, accurate extent of post harvest losses and curing of vegetables to enhance the shelf life since. The proper cleaning or washing before marketing, sorting & grading of vegetables, safe loading, transportation and safe unloading post harvest management practices were regularly adopted by the farmers while cooling & curing of vegetables were occasionally adopted by respondents clearly indicates no storage and processing of produce, essential for better earnings through value addition coupled with increasing food availability and nutritional security of the country. Lack of remunerative minimum support price policy, lower price of vegetables and high cost of inputs especially the hybrid seeds followed by price fluctuation, distress sale due to lower price at time of harvesting, perishable nature of vegetables and decrease in production due to natural calamities were found serious constraints by almost all respondents.